Réponse finale du député de directeur du Bureau Européen de l'ONU au Président du Comité international de la Croix-Rouge . Final Reply from the Deputy Director of the European Office of the United Nations to the President of the International Committee of the Red Cross - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations European Office